ANALISIS KOMPARATIF PENDAPATAN PETANI PADI PENERIMA BANTUAN MODAL PUAP (PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN) DAN PETANI NON PENERIMA BANTUAN MODAL PUAP DI DESA NGARAK KECAMATAN MANDOR KABUPATEN LANDAK - Dewi Kurniati, Sisilia, Marisi Aritonang, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2012)
ABSTRACT In general, the problem of poverty is closely linked to agricultural problems in Indonesia. The worst problem for most Indonesian farmer with limited capital is owned by the farmer. In order to overcome these problems, program Pengembangan Usaha Agribisnis Perdesaan (PUAP). PUAP was one of agriculture in West Kalimantan, especially in the Landak District where have been implemented with the funds as much as Rp.100.000.000,00.- For every poor village or famers federation (Gapoktan). One of the districts that have received the Desa Mandor of the PUAP funding are which is the potential for the development of rice plants, especially in the Desa Ngarak. The PUAP grants distribution were through farmers group federation (Gapoktan) of the certain village. This study aims to analyze the ratio of the average income of rice farmers PUAP and the average income of farmers in Desa Ngarak non PUAP District Mandor Porcupine District. This study aims to analyze the ratio of the average income of rice farmers PUAP and the average income of farmers in the Desa Ngarak non PUAP Sub District Overseer Landak. The Results of data analysis from this study showed the average income of PUAP farmers amounted Rp.16.754.637/Th/Ha, and the average non PUAP farmers income amounted Rp.13.037.452/Th/Ha. The results showed there were differences in the average income of rice farmers PUAP with an average income of rice farmers non PUAP. Where PUAP program has succeeded in increasing significantly the income of rice farmers in the village Ngarak Keywords: Program PUAP, comparative analysis, income rice farmers